Prognostic and Immunotherapeutic Roles of KRAS in Pan-Cancer - Kaixin Yang; Chengyun Li; Yang Liu; Xueyan Gu; Longchang Jiang; Lei Shi (Cells, 2022)
KRAS is one well-established tumor-driver gene associated with cancer initiation, development, and progression. Nonetheless, comparative studies of the relevance of KRAS across diverse tumors remain sparse. We explored the KRAS expression and prognostic values in diverse cancer types via multiple web-based bioinformatics tools, including cBioPortal, Oncomine, PrognoScan, Kaplan–Meier Plotter, etc. We found that KRAS is highly expressed in various malignancies compared to normal cohorts (BRCA, CHOL, ESCA, HNSC, LIHC, LUAD, LUSC, and STAD) and less expressed in COAD, KIRC, READ, and THCA than in normal samples. We observed the dysregulation of the DNA methylation of KRAS in cancers and discovered that numerous oncogenic and tumor-suppressive transcription factors bind the KRAS promoter region. Pan-cancer analysis also showed that a high level of KRAS is associated with poor outcomes. Additionally, KRAS is remarkably correlated with the level of immune cell infiltration and tumorigenic gene signatures. In conclusion, our findings reveal novel insights into KRAS expression and its biological functions in diverse cancer types, indicating that KRAS could serve as a prognostic biomarker and is associated with immune infiltrates.